2022
DOI: 10.3390/jpm12091440
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Circulating Tumor Cells for Predicting Major Histopathological Response after Neoadjuvant Chemoradiotherapy in Patients with Esophageal Cancer

Abstract: Background: A “surgery as needed” approach may be offered to patients with esophageal cancer (EC) who achieve major histopathological response (MaHR) after neoadjuvant chemoradiotherapy (nCRT). However, the utility of clinical response assessment (CRE) for predicting histopathological response to nCRT remains limited. Circulating tumor cells (CTCs) hold promise as biomarkers of response to nCRT. Methods: We analyzed the clinical utility of post-nCRT CTCs, alone or in combination with CRE, in the prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…18259; Stemcell Technologies Inc.) according to the manufacturer's instructions. The methods used for CTC enrichment and counting have been previously described ( 27 , 33 , 34 ). CTCs were not collected from patients experiencing disease progression or death from cancer, as these were the predefined endpoints of the study for predicting survival events.…”
Section: Methodsmentioning
confidence: 99%
“…18259; Stemcell Technologies Inc.) according to the manufacturer's instructions. The methods used for CTC enrichment and counting have been previously described ( 27 , 33 , 34 ). CTCs were not collected from patients experiencing disease progression or death from cancer, as these were the predefined endpoints of the study for predicting survival events.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that CTCs can serve as diagnostic indicators for esophageal cancer and provide insights into distant metastasis ( 72 ). Some studies have also suggested that CTCs can be predictive of the prognosis in patients with esophageal cancer.…”
Section: Mechanism Of Esophageal Cancer Metastasismentioning
confidence: 99%